The sciences by controversies (PerCursos, 2022)
The Sciences have emerged and consolidated over the last few centuries as one the knowledge that most supported everyday life, changing our mode of existence in the world. This did not happen peaceful for scientists, because the Sciences developed as hegemonic knowledge in Modernity through conflicts and controversies. One of the main points of this development arose from the 1960s, when the Sciences gained new faces due to the multiplicity of perspectives, proposals and theories. This occurred due the inclusion, even if they were marginal, for the some subjects and some social segments, that scientists only studied, but these people studied did not have voice in the University. Added to this, the virtual social networks allowed access to the information, among these, the scientific proposals. Paradoxically, the same fact that made access to information and scientific proposals, allowed contestations about Science by some subjects and organized social segments. From this, our main objective of this text is to analyse these controversies to understand how they constituted the Sciences in contemporary times.
Keywords: subject; scientist; society; history of sciences; sociology of sciences